Realising Ainu indigenous rights: a commentary on Hiroshi Maruyama's ‘Japan's post-war Ainu policy. Why the Japanese Government has not recognised Ainu indigenous rights?’ - Nakamura, Naohiro (Polar Record, 2013)
ABSTRACT This commentary reviews Maruyama's article ‘Japan's post-war Ainu policy: why the Japanese Government has not recognised Ainu indigenous rights?’ (Maruyama 2013a), published in this journal. Maruyama criticises the government for its reluctance to enact a new Ainu law to guarantee indigenous rights, even after Japan's ratification of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP). However, in actuality, the government is searching for the foundation of new Ainu policies in the existing legal frameworks and trying to guarantee some elements of indigenous rights. Japan's case suggests the possibility of realising indigenous rights without the enactment of a specific law.